INFLUENCE OF CAPITAL ADEQUACY RATIO (CAR) AND NON PERFOMING LOAN (NPL) ON RETURN ON ASSETS (ROA) ON PT. BANK CENTRAL ASIA TBK.: PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN NON PERFOMING LOAN (NPL) TERHADAP RETURN ON ASSETS (ROA) PADA PT. BANK CENTRAL ASIA TBK. - Nurwita Nurwita (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
This study aims to determine whether there is an effect of Capital Adequacy Ratio (CAR) on Return On Assets (ROA), whether there is an effect of Non Performing Loans (NPL) on Return On Assets (ROA) and whether there is an effect of Capital Adequacy Ratio (CAR) and Non-Performing Loans. Performing Loan (NPL) to Return On Assets (ROA). The variables in this study are CAR and NPL as independent variables and ROA as the dependent variable. Data collection can be obtained through secondary data and literature study. The data were analyzed by calculating the correlation coefficient test, partial t test and simultaneous F test. The results showed that partially CAR had a significant effect on ROA at PT. Bank Central Asia, NPL has no significant effect on ROA at PT. Bank Central Asia, Tbk, and Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) have a significant effect on Return On Assets (ROA).